Sustainable architecture directed by Joe Clokey - Clokey, Joe; san Luis Video Publishing (California : San Luis Video Publishing, 1994)
Discusses how and why sustainable building design can save on the use of nonrenewable resources both in the materials and energy used
Writer, Tora Clokey, Henry Hammer
Host: Tom Bartels
Keywords: Architectural design; Architectural